Freedom of Expression: A Reality and A Myth in India - K. Sinchana; Sathish Kumar, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
This article explores the dualistic nature of freedom of expression in India, framed as both a constitutional reality and a persistent myth. While Article 19(1)(a) provides a robust legal foundation, reinforced by landmark judicial interventions like the Shreya Singhal case, the practical exercise of this right faces significant hurdles. The authors analyze the tension between democratic ideals and restrictive measures, including the misuse of sedition and anti-terror laws, digital censorship, and rising social intolerance. Ultimately, the paper argues that while the judiciary remains a guardian of liberty, true freedom of expression requires a cultural shift toward tolerance to bridge the gap between constitutional promise and lived practice.
Keywords: Article 19(1)(a); Constitutional Democracy; Judicial Interpretation; Digital Censorship; Reasonable Restrictions